Analysis of Pesticide Residue in Tomatoes by Carbon Nanotubes/β‐Cyclodextrin Nanocomposite Reinforced Hollow Fiber Coupled with HPLC. Issue 6 (20th May 2019) - Ding, Yawen; Song, Xinyue; Chen, Juan
Abstract : Abstract: For addressing the issues of pesticide residue analysis characterized by the trace levels of target analytes and the complexity of sample matrices, a selective extracting material, carbon nanotubes (CNTs)/β‐cyclodextrin (β‐CD) nanocomposite reinforced hollow fiber (HF), was developed. CNTs were chemically modified with β‐CD and then the resultant nanocomposite was immobilized into the wall pores and lumen of HF by sol‐gel technology. The reinforced HF was applied to direct‐immersion mode of solid phase microextraction for the determination of carbaryl and 1‐naphthol in tomatoes, coupled with high performance liquid chromatography. The proposed method provided 240‐ and 215‐fold enrichment factors, good linearity in the range of 0.6 to 600 ng/g and 0.2 to 600 ng/g, good repeatability with RSDs of 4.5% and 6.9%, and batch‐to‐batch reproducibility with RSDs of 7.4% and 8.3% for 1‐naphthol and carbaryl, respectively. Moreover, the low limits of detection at 0.05 and 0.15 ng/g for 1‐naphthol and carbaryl, respectively, along with the high recovery in the range of 84.2% to 108.9% were obtained. The results showed that the material combined the respective advantages of CNTs, β‐CD, and HF, thus, exhibiting efficient adsorption property, outstanding molecular recognition performance, and excellent sample clean‐up effect, and it is applicable for pesticide residue analysis in complex matrices. Practical Application: The developed extracting material can be used for pesticide residue analysis of tomatoes. Pesticides, carbaryl, and 1‐naphthol were detected in tomatoes, the most popular vegetable grown and consumed globally. The results supported the necessity to monitor pesticide residue for public health.